An actuating film material and methods of making and using the same

CN122914628APending Publication Date: 2026-10-16BEIJING UNIV OF CHEM TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610849224.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-12
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

因此,如何将MXene的低发射与光热特性与PTFE的疏水保护及光学兼容性相结合,并通过结构设计赋予材料动态自适应的可见光与红外调控能力,是一个重大挑战

Benefits of technology

[0026]This application achieves spectrally selective modulation driven by interlayer stress mismatch by constructing a temperature-actuated unit with an asymmetric hierarchical structure and a bilateral differential optical coating. In low-temperature or no-direct-light environments, the material spreads out flat, exhibiting a white appearance and low infrared emissivity, matching the background of ships or the sea surface. Under moderate temperatures and illumination, the material partially flips, exhibiting blue color and moderate infrared emissivity, matching a low-irradiance background. In high-temperature and high-light environments, the material completely flips, and the ink changes color to yellow, exhibiting high infrared emissivity, matching high-temperature backgrounds such as beaches. This process simultaneously achieves adaptive dynamic matching of visible light and infrared characteristics, while also providing efficient personal thermal management. Furthermore, its excellent superhydrophobic properties endow the material with superior moisture and salt resistance, ensuring long-term stability in harsh environments such as the ocean.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122914628A_ABST
    Figure CN122914628A_ABST
Patent Text Reader

Abstract

The application provides an actuating film material and a preparation method and application method thereof; the actuating film material is a multilayer asymmetric structure, comprising a nanoporous film layer, an MXene layer and a PTFE layer; wherein: the nanoporous film layer and the PTFE layer are respectively located on the two sides of the MXene layer, and the surface of the side of the PTFE layer away from the MXene layer is coated with a thermochromic ink layer; the actuating film material generates reversible deformation through interlayer thermal strain mismatch under the driving of temperature change, thereby realizing the synchronous regulation of infrared emissivity and visible light reflection characteristics. The preparation method comprises the following steps: preparing an MXene slurry; performing single-sided hydrophilic modification on a PTFE film and a nanoporous film; spraying a thermochromic ink on one side surface of the PTFE film; and compounding the prepared MXene slurry between the hydrophilically modified nanoporous film and the PTFE film, to prepare an actuating film material with a nanoporous film layer, an MXene layer and a PTFE layer in a three-layer asymmetric structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of stealth and thermal management materials technology, specifically to an actuation film material with dynamic infrared-visible light stealth, moisture and salt resistance and thermal management functions, as well as its preparation method and application method. Background Technology

[0002] With the rapid development of multi-band fusion reconnaissance technology, military targets face extremely high exposure risks in complex and multi-scenario environments. Traditional single-band or static camouflage materials are no longer sufficient to meet the needs of modern battlefield reconnaissance technologies that employ multiple bands and multiple modes. Accordingly, stealth materials with infrared-visible dual-band camouflage capabilities are of great significance for gaining the initiative in warfare.

[0003] Visible light camouflage primarily relies on static color matching strategies using pigments or dyes to blend with the background environment, while infrared stealth materials often employ low infrared emissivity strategies such as metal or metal oxide coatings to reduce the likelihood of target detection. However, materials that achieve high visible light reflectivity or distinctive color characteristics often possess high emissivity in the infrared band; typical low infrared emissivity materials typically exhibit a metallic luster or dark appearance, making them unsuitable for visible light camouflage. This inherent conflict in spectral characteristics makes infrared-visible dual-band camouflage difficult to integrate within existing material systems.

[0004] In real-world battlefield environments, such as transitions from sea to beach, the visible light and infrared radiation characteristics of the background change significantly with environmental conditions. In low-radiation backgrounds (like sea), simply reducing the infrared emissivity of thermal targets can achieve stealth; however, in high-radiation backgrounds (like beach), low emissivity can actually enhance the radiation contrast between the target and the background, leading to decreased camouflage effectiveness or even reverse exposure. Furthermore, in high-humidity, high-salt environments such as the ocean, material surfaces are prone to oxidation or salt residue, significantly increasing infrared emissivity and causing rapid degradation of infrared camouflage capabilities. Therefore, developing adaptive infrared-visible dual-band camouflage materials with environmental responsiveness, while also possessing good moisture and salt resistance, has become a key direction for achieving stable and coordinated stealth in multiple scenarios.

[0005] MXene (a two-dimensional transition metal carbon / nitride material), as an emerging two-dimensional material, possesses metal-like low infrared emissivity and excellent photothermal conversion capabilities, making it an ideal candidate for infrared stealth and thermal management. However, its inherent dark appearance and susceptibility to oxidative degradation limit its application in multi-scenario, long-term visible-infrared compatible stealth applications. Polytetrafluoroethylene (PTFE) exhibits excellent chemical inertness, superhydrophobicity, and high transmittance in the mid- and far-infrared bands, effectively protecting the functional layer without causing optical interference. Therefore, combining the low emissivity and photothermal properties of MXene with the hydrophobic protection and optical compatibility of PTFE, and endowing the material with dynamic adaptive visible-infrared control capabilities through structural design, presents a significant challenge. Summary of the Invention

[0006] Therefore, the purpose of this application is to provide an actuation membrane material with dynamic infrared-visible light stealth, moisture and salt resistance and thermal management functions, as well as its preparation method and application method.

[0007] According to a first aspect of this application, an actuation membrane material with dynamic infrared-visible light stealth, moisture and salt resistance, and thermal management functions is provided. The actuation membrane material has a multilayer asymmetric structure, comprising a nanoporous membrane layer, a transition metal carbide / nitride (MXene) layer, and a polytetrafluoroethylene (PTFE) layer. The nanoporous membrane layer and the PTFE layer are located on opposite sides of the MXene layer, and the surface of the PTFE layer facing away from the MXene layer is coated with a thermochromic ink layer. The actuation membrane material undergoes reversible deformation through interlayer thermal strain mismatch driven by temperature changes, thereby achieving synchronous control of infrared emissivity and visible light reflectivity.

[0008] Specifically, the structural relationship between the nanoporous membrane layer, the MXene layer, and the PTFE layer is as follows: (i) Stacking sequence (from outside to inside): The actuation membrane material is a four-layer composite structure, consisting of: a nanoporous membrane layer (outermost layer, one side), an MXene layer (middle layer), a PTFE layer (the other side of the base layer), and a thermochromic ink layer (outermost functional coating) coated on the surface of the PTFE layer facing away from the MXene layer.

[0009] (II) Functional and connectivity relationships between layers: The nanoporous membrane layer is located on the outermost layer (one side) and is directly composited to the outer surface of the MXene layer (the other side opposite the PTFE layer). Its functions are: to provide superhydrophobic protection (contact angle ≥150°), resistance to salt residue, and to reflect visible light through Mie scattering (presenting a white or blue background); it also has high infrared transmittance and does not interfere with the infrared modulation of the internal MXene layer.

[0010] The MXene layer is located in the middle layer, with one side composited with the hydrophilic modified surface of the PTFE layer and the other side composited with the nanoporous membrane layer. Its functions are: to provide low infrared emissivity (infrared stealth), excellent photothermal conversion capability (thermal management), and a high modulus confinement layer (forming a thermal strain mismatch with the PTFE layer to drive actuation).

[0011] The PTFE layer serves as the base layer on the other side. Its hydrophilic modified side is composited with the MXene layer, while its unmodified side (the side facing away from the MXene layer) is coated with thermochromic ink. Its functions include providing a high coefficient of thermal expansion (actuator layer), chemical inertness, high mid- and far-infrared transmittance, and a supporting role.

[0012] The thermochromic ink layer is sprayed onto the side of the PTFE layer facing away from the MXene layer, and its function is to provide visible light dynamic camouflage (achieving reversible color switching from blue to yellow within the range of 40 to 50°C).

[0013] (III) Core Design Considerations for Asymmetric Structures: ① Thermal strain mismatch-driven actuation: The PTFE layer has a high coefficient of thermal expansion (approximately 10). -4 (on the order of / K), while the MXene layer has a lower coefficient of thermal expansion (approximately 10). -6 (on the order of / K). When the temperature changes, a significant strain mismatch occurs between the two layers, and due to the structural asymmetry (one side is high-expansion PTFE, and the other side is low-expansion MXene+ nanoporous membrane), the material undergoes reversible bending deformation towards the MXene layer side.

[0014] ② Dual-sided optical function separation: Under low temperature / weak light, the nanoporous membrane side faces outward, exhibiting low infrared emissivity + blue / white appearance (matching the sea / sky); under high temperature / strong light, the material is actuated and flipped, the thermochromic ink side faces outward, exhibiting high infrared emissivity + yellow appearance (matching the beach / sand).

[0015] ③ Interface bonding method: Both the PTFE membrane and the nanoporous membrane are modified with hydrophilic coating on one side to ensure a strong interface bond with the hydrophilic MXene slurry; the MXene layer is coated onto the hydrophilic modified surface of the PTFE membrane; the nanoporous membrane is coated onto the other side of the MXene layer.

[0016] In some embodiments, the nanoporous membrane is one of the following: PTFE membrane, polyethylene membrane, or nylon membrane.

[0017] In some embodiments, the thickness of the nanoporous membrane layer is 20-50 μm, the thickness of the MXene layer is 40-60 μm, the thickness of the PTFE layer is 50-70 μm, the thickness of the thermochromic ink layer is 30-50 μm, and the overall thickness of the actuation membrane material is 140-230 μm.

[0018] In some embodiments, the thermochromic ink layer comprises crystal violet lactone, bisphenol A, octadecyl alcohol microcapsules and a yellow pigment, which can achieve reversible color switching from blue to yellow in the range of 40 to 50°C.

[0019] In some embodiments, on a 36°C hot plate, the actuation angle of the actuation membrane material reaches 150° or more.

[0020] According to a second aspect of this application, a method for preparing an actuation membrane material with dynamic infrared-visible light stealth, moisture and salt resistance, and thermal management functions is provided, comprising the following steps: preparing an MXene slurry; performing one-sided hydrophilic modification on a PTFE membrane and a nanoporous membrane; spraying a thermochromic ink onto one side surface of the PTFE membrane; and combining the prepared MXene slurry between the hydrophilically modified nanoporous membrane and the PTFE membrane to prepare an actuation membrane material with a three-layer asymmetric structure consisting of a nanoporous membrane layer, an MXene layer, and a PTFE layer.

[0021] In some embodiments, the step of preparing the MXene slurry further includes: adding titanium aluminum carbide (Ti3AlC2) powder to concentrated hydrochloric acid (HCl) containing dissolved lithium fluoride (LiF), and etching at a temperature of 35–40°C for 36–48 hours to prepare titanium carbide (Ti3C2T). x (An MXene material) suspension; filtered and washed with water, centrifuged at 5000-10000 rpm until the pH value is close to 7; then sonicated under nitrogen and ice bath conditions for 0.5-1 hour, and centrifuged at 2500-4000 rpm for 0.5-1 hour to obtain one or more MXene suspensions.

[0022] In some embodiments, the single-sided hydrophilic modification step further includes: dissolving 5 parts by weight of dopamine hydrochloride in Tris buffer solution to prepare a dopamine buffer solution with a pH of 7-9; immersing the nanoporous membrane and PTFE membrane in the prepared buffer solution for 12-36 hours to form a hydrophilic polydopamine coating on one side.

[0023] In some embodiments, the step of spraying thermochromic ink further includes: spraying thermochromic ink onto the side surface of the PTFE film opposite to the MXene layer, and drying it at room temperature so that the thickness of the dried thermochromic ink layer reaches 30-50 μm.

[0024] In some embodiments, the preparation steps of the actuation membrane material further include: uniformly coating MXene slurry onto the hydrophilic modified surface of the PTFE membrane in a single direction using an 800-2000 μm blade coater; adjusting the blade gap and the number of coats to achieve a dried MXene layer thickness of 40-60 μm; composite a nanoporous membrane onto the surface of the MXene layer; and drying at room temperature to obtain an actuation membrane material with a multilayer asymmetric structure consisting of a nanoporous membrane layer, an MXene layer, and a PTFE layer.

[0025] According to a third aspect of this application, a method for applying an actuating membrane material is provided, wherein the actuating membrane material is the aforementioned actuating membrane material, or is a... Step 1: Cover or adhere the actuation membrane material to the outer surface of the target object, with the nanoporous membrane layer facing outwards; Step 2: When the ambient temperature is lower than the first preset temperature or the sunlight intensity is lower than the first preset light intensity, the actuation membrane material is kept in a flat and spread state, the nanoporous membrane layer faces outward and presents a white appearance, and the MXene layer provides low infrared emissivity, so that the target object can be camouflaged and blended with the ship or low temperature and low radiation background in the visible light and infrared bands. Step 3: When the ambient temperature is between the first preset temperature and the second preset temperature, or when the sunlight intensity is between the first preset light intensity and the second preset light intensity, the actuation film material undergoes partial reversible bending deformation due to interlayer thermal strain mismatch, causing the thermochromic ink layer to be partially exposed and displaying the first visible light color (low temperature blue). At the same time, the actuation film material displays a medium infrared radiation intensity, enabling the target object to achieve camouflage and blending with the low-irradiance background. Step 4: When the ambient temperature is higher than the second preset temperature or the sunlight intensity is higher than the second preset light intensity, the actuation film material undergoes a fully reversible bending deformation due to interlayer thermal strain mismatch, so that the thermochromic ink layer is completely exposed to the outside. Under temperature stimulation, the thermochromic ink layer changes from blue to the second visible light color (yellow). At the same time, the actuation film material exhibits high infrared radiation intensity, so that the target object can achieve camouflage and blend with the high-irradiance background (such as a beach).

[0026] This application achieves spectrally selective modulation driven by interlayer stress mismatch by constructing a temperature-actuated unit with an asymmetric hierarchical structure and a bilateral differential optical coating. In low-temperature or no-direct-light environments, the material spreads out flat, exhibiting a white appearance and low infrared emissivity, matching the background of ships or the sea surface. Under moderate temperatures and illumination, the material partially flips, exhibiting blue color and moderate infrared emissivity, matching a low-irradiance background. In high-temperature and high-light environments, the material completely flips, and the ink changes color to yellow, exhibiting high infrared emissivity, matching high-temperature backgrounds such as beaches. This process simultaneously achieves adaptive dynamic matching of visible light and infrared characteristics, while also providing efficient personal thermal management. Furthermore, its excellent superhydrophobic properties endow the material with superior moisture and salt resistance, ensuring long-term stability in harsh environments such as the ocean. Attached Figure Description

[0027] Figure 1 This is a flowchart illustrating the preparation method of the actuation membrane material with dynamic infrared-visible light stealth, moisture and salt resistance, and thermal management functions as described in this application.

[0028] Figure 2 This is a schematic flowchart illustrating the preparation method of the actuation membrane material with dynamic infrared-visible light stealth, moisture and salt resistance, and thermal management functions according to this application.

[0029] Figure 3 This is a digital image showing the actuation of the actuation membrane material prepared in Example 1 of this application when placed on a 36°C hot stage.

[0030] Figure 4 The actuation performance of the actuation film materials with different MXene layer thicknesses prepared in Example 2 of this application under different temperatures and light intensities is shown in the figure.

[0031] Figure 5 Infrared stealth performance of the actuation film material prepared in Example 1 of this application under low-radiation and high-radiation backgrounds.

[0032] Figure 6 This is a diagram showing the moisture-repellent and salt-resistant properties of the actuation membrane material prepared in Example 1 of this application.

[0033] Figure 7 This is a graph showing the color change performance of the actuation membrane material prepared in Example 1 of this application at different temperatures.

[0034] Figure 8 The diagram shows the thermal management performance of the actuation membrane material prepared in Example 1 of this application under different environmental conditions.

[0035] Figure 9 The image shows the infrared-visible dual-band synergistic stealth demonstration of the actuation membrane material prepared in Example 1 of this application under simulated sea surface and beach scenarios. Detailed Implementation

[0036] The following detailed embodiments illustrate the essence of the technical solution of this application. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of this application. Experimental methods in the following embodiments without specific conditions are generally performed under conventional conditions or as recommended by the manufacturer. Unless otherwise specified, all reagents and materials used in this application are commercially available.

[0037] This application provides an actuation film material with dynamic infrared-visible light stealth, moisture and salt resistance, and thermal management functions, along with its preparation and application methods. The material comprises an asymmetric structure consisting of a PTFE actuation layer with anisotropic thermal expansion behavior and a high-modulus MXene confinement layer, achieving thermal actuation. Simultaneously, a nanoporous membrane layer provides hydrophobic protection and modulates light absorption, while a thermochromic ink layer endows the material with dynamic visible light color-changing capabilities. Through multi-layer synergy, this material can reversibly and synchronously switch between infrared radiation characteristics and visible light color under temperature and ambient light stimulation, thereby achieving adaptive dual-band stealth in different background environments.

[0038] This application provides an actuation membrane material with dynamic infrared-visible light stealth, moisture and salt resistance, and thermal management functions. The actuation membrane material has a multilayer asymmetric structure, comprising a nanoporous membrane layer, an MXene layer, and a PTFE layer. The nanoporous membrane layer and the PTFE layer are located on opposite sides of the MXene layer, and the surface of the PTFE layer facing away from the MXene layer is coated with a thermochromic ink layer. The actuation membrane material undergoes reversible deformation through interlayer thermal strain mismatch driven by temperature changes, thereby achieving synchronous control of infrared emissivity and visible light reflectivity.

[0039] In some embodiments, the nanoporous membrane is one of the following: PTFE membrane, polyethylene membrane, or nylon membrane.

[0040] In some embodiments, the thickness of the nanoporous membrane layer is 20-50 μm, the thickness of the MXene layer is 40-60 μm, the thickness of the PTFE layer is 50-70 μm, the thickness of the thermochromic ink layer is 30-50 μm, and the overall thickness of the actuation membrane material is 140-230 μm.

[0041] In some embodiments, the thermochromic ink layer comprises crystal violet lactone, bisphenol A, octadecyl alcohol microcapsules and a yellow pigment, which can achieve reversible color switching from blue to yellow in the range of 40 to 50°C.

[0042] In some embodiments, on a 36°C hot plate, the actuation angle of the actuation membrane material reaches 150° or more.

[0043] The following further clarifies the interlayer structural relationship of the actuation membrane material: 1. Stacking sequence (from outside to inside): The actuation membrane material is a four-layer composite structure, consisting of: a nanoporous membrane layer (outermost layer, one side), an MXene layer (middle layer), a PTFE layer (the other side of the base layer), and a thermochromic ink layer (outermost functional coating) coated on the surface of the PTFE layer facing away from the MXene layer.

[0044] 2. Functions and connections of each layer: Nanoporous membrane layer: Located on the outermost layer (one side), directly composited to the outer surface of the MXene layer (the other side opposite the PTFE layer). Its functions include: providing superhydrophobic protection (contact angle ≥150°), resistance to salt residue, reflecting visible light through Mie scattering (presenting a white or blue background); and having high infrared transmittance without interfering with the infrared modulation of the internal MXene layer.

[0045] MXene layer: Located in the middle layer, it is composited with the hydrophilic modified surface of the PTFE layer on one side and with the nanoporous membrane layer on the other side. Its functions include: providing low infrared emissivity (infrared stealth), excellent photothermal conversion capability (thermal management), and a high modulus confinement layer (forming a thermal strain mismatch with the PTFE layer to drive actuation).

[0046] PTFE layer: As the base layer on the other side, its hydrophilic modified side is composited with the MXene layer, and its unmodified side (the side facing away from the MXene layer) is coated with thermochromic ink. Its functions include: providing a high coefficient of thermal expansion (actuator layer), chemical inertness, high mid- and far-infrared transmittance, and a supporting role.

[0047] Thermochromic ink layer: Sprayed on the side of the PTFE layer facing away from the MXene layer, its functions include: providing dynamic camouflage in visible light (achieving reversible color switching from blue to yellow in the range of 40 to 50°C).

[0048] 3. Key design considerations for asymmetric structures: ① Thermal strain mismatch-driven actuation: The PTFE layer has a high coefficient of thermal expansion (approximately 10). -4 (on the order of / K), while the MXene layer has a lower coefficient of thermal expansion (approximately 10). -6 (on the order of / K). When the temperature changes, a significant strain mismatch occurs between the two layers, and due to the structural asymmetry (one side is high-expansion PTFE, and the other side is low-expansion MXene+ nanoporous membrane), the material undergoes reversible bending deformation towards the MXene layer side.

[0049] ② Dual-sided optical function separation: Under low temperature / weak light, the nanoporous membrane side faces outward, exhibiting low infrared emissivity + blue / white appearance (matching the sea / sky); under high temperature / strong light, the material is actuated and flipped, the thermochromic ink side faces outward, exhibiting high infrared emissivity + yellow appearance (matching the beach / sand).

[0050] ③ Interface bonding method: Both the PTFE membrane and the nanoporous membrane are modified with hydrophilic coating on one side to ensure a strong interface bond with the hydrophilic MXene slurry; the MXene layer is coated onto the hydrophilic modified surface of the PTFE membrane; the nanoporous membrane is coated onto the other side of the MXene layer.

[0051] Example 1: Preparation of Actuation Membrane Material This embodiment prepares an actuation film material with dynamic infrared-visible light stealth, moisture and salt resistance, and thermal management functions. Its structure fully conforms to the multilayer asymmetric structure described above in the material structure relationship description. Figure 1 A flowchart of the preparation method of the actuator membrane material of this application is shown. Figure 2 A flowchart illustrating its process. For example... Figure 1 , Figure 2 As shown, the preparation method of the actuation film material with dynamic infrared-visible light stealth, moisture and salt resistance and thermal management functions of this application includes the following steps: Step S1: Prepare MXene slurry.

[0052] In some embodiments, the step of preparing the MXene slurry further includes: adding Ti3AlC2 powder to concentrated HCl containing dissolved LiF, and etching at a temperature of 35–40°C for 36–48 hours to prepare Ti3C2T. x (An MXene material) suspension; filtered and washed with water, centrifuged at 5000-10000 rpm until the pH value is close to 7; then sonicated under nitrogen and ice bath conditions for 0.5-1 hour, and centrifuged at 2500-4000 rpm for 0.5-1 hour to obtain one or more MXene suspensions.

[0053] In the specific implementation process, 1g of LiF powder was dissolved in 20mL of concentrated HCl and thoroughly mixed under magnetic stirring. Then, 1g of Ti3AlC2 powder (200 mesh, purity >98%) was slowly added, and the mixture was continuously stirred and etched at a temperature of 35-40℃ for 36-48 hours to obtain Ti3C2T. x(An MXene material) suspension. The etched suspension was repeatedly filtered and washed with deionized water, then centrifuged at 5000–10000 rpm (5 minutes each time) until the pH of the supernatant was close to 7. Next, it was sonicated for 0.5–1 hour (200W) under nitrogen protection and an ice bath, then centrifuged at 2500–4000 rpm for 0.5–1 hour, and the supernatant was collected to obtain one or more layers of MXene suspension. The suspension was concentrated to the desired concentration (approximately 10–20 mg / mL) by vacuum-assisted filtration to obtain the MXene slurry.

[0054] Step S2: Perform one-sided hydrophilic modification on PTFE membranes and nanoporous membranes.

[0055] In some embodiments, the single-sided hydrophilic modification step further includes: dissolving 5 parts by weight of dopamine hydrochloride in Tris buffer solution to prepare a dopamine buffer solution with a pH of 7-9; immersing the nanoporous membrane and PTFE membrane in the prepared buffer solution for 12-36 hours to form a hydrophilic polydopamine coating on one side.

[0056] In the specific implementation process, a nanoporous polytetrafluoroethylene (nPTFE) membrane with a thickness of 20–50 μm (pore size approximately 0.1–1 μm) is selected, and a commercially available PTFE membrane with a thickness of 50–70 μm is selected. A dopamine buffer solution is prepared by dissolving 5 g of dopamine hydrochloride in 1 L of Tris buffer (10 mM, pH 8.5), and the pH is adjusted to 7–9. The nPTFE and PTFE membranes are washed separately with ethanol and deionized water, respectively. One surface is protected with adhesive tape, and the unprotected side is then immersed in the dopamine buffer solution at room temperature for 12–36 hours to form a hydrophilic polydopamine coating on one side. After removal, the membranes are rinsed with deionized water and dried with nitrogen gas for later use.

[0057] Step S3: Spray thermochromic ink.

[0058] This step specifically involves spraying thermochromic ink onto one side of the PTFE membrane.

[0059] In some embodiments, the step of spraying thermochromic ink further includes: spraying thermochromic ink onto the side surface of the PTFE film opposite to the MXene layer, and drying it at room temperature so that the thickness of the dried thermochromic ink layer reaches 30-50 μm.

[0060] In the specific implementation process, the thermochromic ink formulation is as follows: 2g of crystal violet lactone (CVL, thermochromic dye), 4g of bisphenol A (developer), 10g of octadecyl alcohol (solvent), and 0.5g of yellow pigment (such as benzidine yellow). These are prepared into microcapsules with a particle size of approximately 1-5μm using a microencapsulation process, and then dispersed in an aqueous acrylic resin to form an ink with a solid content of approximately 30%. The ink is then uniformly sprayed onto the unmodified side of the PTFE membrane (i.e., the side facing away from the MXene layer) using a spray gun (0.5mm nozzle, 0.2-0.3MPa air pressure), and dried at room temperature to achieve a dried thermochromic ink layer thickness of 30-50μm. This ink can achieve a reversible color switch from blue to yellow within the temperature range of 40-50℃.

[0061] Step S4: Prepare composite actuation membrane material.

[0062] Specifically, this step involves: combining the prepared MXene slurry between the hydrophilically modified nanoporous membrane and the PTFE membrane to prepare an actuation membrane material with a three-layer asymmetric structure consisting of a nanoporous membrane layer, an MXene layer, and a PTFE layer.

[0063] In some embodiments, the preparation steps of the actuation membrane material further include: uniformly coating MXene slurry onto the hydrophilic modified surface of the PTFE membrane in a single direction using an 800-2000 μm blade coater; adjusting the blade gap and the number of coats to achieve a dried MXene layer thickness of 40-60 μm; composite a nanoporous membrane onto the surface of the MXene layer; and drying at room temperature to obtain an actuation membrane material with a multilayer asymmetric structure consisting of a nanoporous membrane layer, an MXene layer, and a PTFE layer.

[0064] In the specific implementation process, an 800-2000μm doctor blade is used to uniformly coat the MXene slurry onto the hydrophilic modified surface of the PTFE membrane in a single direction. By adjusting the doctor blade gap and the number of coats, the thickness of the dried MXene layer reaches 40-60μm. In this embodiment, the thickness of the dried MXene layer is controlled to be 52μm. Then, the aforementioned single-sided hydrophilic modified nPTFE membrane (nanoporous membrane) is gently covered on the surface of the wet MXene slurry with its hydrophilic side facing the MXene layer. Slight pressure is applied to ensure tight adhesion, and the membrane is dried at room temperature for 12 hours to obtain an actuation membrane material with a multilayer asymmetric structure of an nPTFE membrane layer, an MXene layer, and a PTFE layer. Measurements showed that the overall thickness of the obtained actuator membrane material was approximately 160 μm (of which the nPTFE layer was approximately 35 μm thick, the MXene layer 52 μm, the PTFE layer 60 μm, and the ink layer approximately 40 μm), meeting the thickness range (nanoporous membrane layer 20–50 μm, MXene layer 40–60 μm, PTFE layer 50–70 μm, color-changing ink layer 30–50 μm, overall 140–230 μm). Furthermore, the nanoporous membrane was a PTFE membrane.

[0065] Example 2: Actuation membrane materials with different MXene layer thicknesses Following the method of Example 1, only the blade gap and the number of coats in step S4 were changed to prepare actuation membrane materials with MXene layer thicknesses of 40 μm, 46 μm, 52 μm, and 60 μm after drying. All other conditions were exactly the same as in Example 1. The four actuation membrane materials obtained were designated MXene-40, MXene-46, MXene-52, and MXene-60, respectively. The thicknesses of each layer in these samples were all within the defined range.

[0066] Example 3: Actuation Performance Test This embodiment tests the actuation performance of actuation film materials with different MXene layer thicknesses prepared in Example 2, verifying their ability to generate reversible deformation through interlayer thermal strain mismatch driven by temperature changes.

[0067] (1) Actuation angle on a 36℃ hot stage: Cut the actuation membrane sample into strips of 1cm × 3cm, place them on the surface of a 36℃ constant temperature hot stage, and record the maximum angle of bending at the free end of the sample. For example... Figure 4 As shown in section a, the actuation angles of MXene-40, MXene-46, MXene-52, and MXene-60 reach 55°, 118°, 151°, and 128°, respectively. Among them, MXene-52 (thickness 52μm) exhibits the best actuation performance, with an actuation angle of 151°, satisfying the requirement that "on a 36° hot stage, the actuation angle of the actuation film material reaches more than 150°".

[0068] (2) Actuation angle at different ambient temperatures: The four actuation membrane samples were placed at ambient temperatures of 20℃, 30℃, 40℃, 50℃, and 60℃ respectively (using a constant temperature chamber), and their actuation angles were measured. Figure 4 As shown in section b, the actuation angle is approximately 25° at 20°C; approximately 60° at 30°C; up to 260° at 40°C; up to 380° at 50°C; and up to 440° at 60°C. The results indicate that this actuation film material exhibits significantly tunable actuation behavior over a wide temperature range, and the actuation angle increases with increasing temperature.

[0069] (3) Actuation angle under different simulated solar light intensities: Using a simulated solar light source (AM 1.5G filter, light intensity adjustable, 1 solar light intensity (1 Sun) ≈ 1000 W / m 2 The four actuation membrane samples were exposed to sunlight intensities of 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, and 1.0, respectively, and the actuation angles were measured. Figure 4 As shown in section c, under 0.4 solar intensity, the actuation angle is approximately 220°; approximately 240° under 0.5 solar intensity; approximately 280° under 0.6 solar intensity; approximately 300° under 0.7 solar intensity; approximately 340° under 0.8 solar intensity; approximately 369° under 0.9 solar intensity; and up to 360° under 1.0 solar intensity. This demonstrates that the material can achieve a wide range of actuation adjustment under natural light conditions.

[0070] Example 4: Infrared Stealth Performance Test In this embodiment, the infrared camouflage performance of the actuation film material (MXene-52) prepared in Example 1 was tested to verify that "it can generate reversible deformation through interlayer thermal strain mismatch under temperature change, thereby achieving synchronous control of infrared emissivity and visible light reflectance characteristics".

[0071] (1) Low-radiation background (simulated sea surface): The ambient temperature was set to 20°C, and a simulated solar light source was used to provide 0.6 solar intensity. The background was a black container filled with seawater, with a surface temperature stable at 20°C. The target was simulated skin at 36°C (simulated skin material was covered on an electrically heated copper plate). The infrared radiation temperature of the target and background was recorded using an infrared thermal imager (FLIR E60).

[0072] The results are as follows Figure 5As shown in sections a and b: without camouflage, the infrared radiation temperature difference between the simulated skin (36℃) and the background (20℃) is 9.3℃, and the target is clearly visible in the thermal image. After covering with the actuation film of Example 1, the actuation film remains flat and spread out at a lower temperature (nanoporous membrane side facing outward), its surface radiation temperature decreases to 27.3℃, and the temperature difference with the background is reduced to 1.8℃. In the infrared thermal image, the target and the background are basically integrated, achieving a good infrared stealth effect.

[0073] (2) High-radiation background (simulated beach): The ambient temperature was set to 30°C, and a simulated solar light source was used to provide 1.0 solar intensity. The background was dry sand (2cm thick), and the surface temperature rose to approximately 58°C under illumination. The target was simulated skin at 36°C. The control sample was ordinary cotton cloth.

[0074] The results are as follows Figure 5 As shown in sections c and d: Without camouflage, the target (36℃) temperature is significantly lower than the background (58℃), with a temperature difference of 22℃, resulting in exposed cold spots. After covering with the actuation film, the material undergoes actuated flipping under strong photothermal drive, exposing a high-emissivity thermochromic ink layer (thermochromic ink side facing outwards). The surface radiation temperature rises to 63.5℃, with a temperature difference of only 2.1℃ between the target and the background (sand surface temperature approximately 61.4℃), successfully achieving compensated infrared stealth against a high-temperature background. In contrast, the target surface radiation temperature covered with cotton cloth still has a temperature difference of 22.6℃ with the background, resulting in extremely poor camouflage. This experiment demonstrates that the material of this application can synchronously regulate infrared emissivity and visible light reflectance characteristics through temperature-driven reversible deformation.

[0075] Example 5: Moisture-repellent and salt-resistant performance test This embodiment tests the seawater corrosion resistance and salt resistance of the actuation membrane material prepared in Example 1 to verify its moisture and salt resistance.

[0076] (1) Salt spray / seawater immersion test: The actuation membrane sample was completely immersed in artificial seawater (prepared according to ASTM D1141 standard) for 2 hours daily, and then removed and allowed to air dry at room temperature. This constitutes one cycle. The cycle was repeated for 30 consecutive days. Samples were taken every 5 days to measure the sample mass, actuation angle, and infrared camouflage effect against a target at 36°C.

[0077] The results are as follows Figure 6 As shown in section a: after 30 days of cycling, the mass increase of the actuated membrane remained below 0.1 mg, indicating its efficient inhibition of salt residue. Under one solar irradiation, after 30 days of immersion, its maximum dynamic angle remained stable at 362.4° (initial value 360°), with a decay of less than 1°. When covered with a target at 36°C, the surface radiation temperature change of the actuated membrane was less than 1°C, demonstrating excellent oxidation resistance and salt corrosion resistance.

[0078] (2) Surface wettability test: The static water contact angle of the nanoporous membrane side of the actuated membrane material was tested using a contact angle meter (OCA20). The results showed a contact angle of 152°, achieving a superhydrophobic state. Figure 6 As shown in section b, when a droplet of artificial seawater (approximately 10 μL) falls onto the surface of a superhydrophobic actuator membrane tilted at 30°, the droplet rolls off rapidly within one second, leaving no trace on the surface. In contrast, droplets on the surface of the comparative pure MXene membrane (without a nanoporous protective layer) cannot slide off, leaving a noticeable high-infrared emission area after drying (due to salt residue causing increased emissivity). This demonstrates that the nanoporous membrane layer of this application provides excellent water-repellent and self-cleaning properties, effectively protecting the internal MXene layer from erosion in a humid salt spray environment, achieving moisture and salt resistance.

[0079] Example 6: Visible Light Color Changing Performance Test This embodiment tests the thermochromic properties of the actuation film material prepared in Example 1, verifying that the thermochromic ink layer achieves reversible color switching from blue to yellow within the range of 40-50℃.

[0080] The actuation membrane samples were placed on hot stages at different temperatures (room temperature, 40℃, 45℃, 50℃, 55℃, and 60℃), and their color changes were recorded using a digital camera. The results are as follows: Figure 7 As shown: At room temperature (approximately 25°C), the actuation film appears blue (from the low-temperature state of the thermochromic ink). When the temperature rises to 45°C, the ink layer completes a rapid color change from blue to yellow within approximately 5 seconds. On a 55°C hot stage, the color change time is shortened to 2 seconds. When the temperature drops to room temperature, the color reversibly reverts to blue. This color change process can be repeated more than 50 times without significant decay. This demonstrates that the thermochromic ink layer of this application achieves rapid and reversible color switching within the 40–50°C range.

[0081] Example 7: Personal Thermal Management Performance Test This embodiment tests the thermal management performance of the actuation membrane material prepared in Example 1 under different environmental conditions.

[0082] Test setup: The simulated skin is an electrically heated copper plate covered with medical-grade silicone to simulate the heat capacity of human skin. An actuator membrane covers the simulated skin, with thermocouple temperature sensors positioned between them. The ambient temperature is controlled by a constant temperature chamber, and simulated sunlight provides illumination.

[0083] (1) Low temperature and no light environment (10℃, 0 Sun): such as Figure 8As shown in part a, the equilibrium temperature of exposed simulated skin is 25.0℃, which is lower than normal body temperature. After covering with cotton cloth, the interface equilibrium temperature is 32.8℃. After covering with the actuation membrane of this application, the interface equilibrium temperature is 33.8℃, which is 1.0℃ higher than that of the cotton cloth, thus providing a heat-insulating effect.

[0084] (2) Low-temperature light environment (10℃, 0.5 Sun): such as Figure 8 As shown in section b, the equilibrium temperature of bare simulated skin is 26.0℃. After covering with cotton cloth, the interface equilibrium temperature is 32.3℃. After covering with the actuator membrane, due to the photothermal conversion effect of the MXene layer, the interface temperature rises to 36.3℃, which is 4.0℃ higher than that of cotton cloth, close to normal body temperature, significantly improving thermal comfort.

[0085] (3) High temperature and no light environment (40℃, 0 Sun): such as Figure 8 As shown in section c, the equilibrium temperature of exposed simulated skin is 37.3℃. After covering with cotton cloth, the interface temperature rises to 39.2℃ due to the heat insulation effect, which is higher than normal body temperature, causing overheating discomfort. After covering with the actuation membrane, the interface equilibrium temperature is only 37.4℃, almost the same as that of exposed skin, indicating that the actuation membrane can effectively dissipate heat at high temperatures.

[0086] (4) High temperature and light environment (40℃, 1 Sun): such as Figure 8 As shown in section d, the equilibrium temperature of exposed simulated skin rises to 40.7°C. After covering with cotton cloth, the interface temperature reaches as high as 42.3°C, indicating significant overheating. After covering with the actuation membrane, the interface equilibrium temperature is controlled at 41.0°C, only slightly higher than that of exposed skin, far superior to that of cotton cloth, demonstrating excellent high-temperature heat dissipation performance. This embodiment proves that the material of this application also possesses efficient personal thermal management capabilities.

[0087] Example 8: Application of Actuation Membrane Materials This embodiment provides a method for applying an actuating membrane material, wherein the actuating membrane material is the one described above, or an actuating membrane material prepared by the preparation method provided in Embodiment 1 above. The specific steps of the application method are as follows: Step 1: Cover or attach the actuation membrane material to the outer surface of the target object (e.g., a simulated human body or military equipment), with the nanoporous membrane layer facing outwards.

[0088] Step 1: Cover or attach the actuation membrane material to the outer surface of the target object (e.g., a ship, individual soldier equipment, or a military vehicle), with the nanoporous membrane layer facing outwards.

[0089] Step Two: When the ambient temperature is lower than a first preset temperature (e.g., 25°C) or the sunlight intensity is lower than a first preset light intensity (e.g., 0.3 times the sunlight intensity), the actuation membrane material is kept in a flat, spread-out state. At this time, the outward-facing nanoporous membrane layer appears white, while the MXene layer provides low infrared emissivity (approximately 0.2-0.3), allowing the target object to blend seamlessly with the ship or low-temperature, low-emissivity background in both visible and infrared bands. This state is suitable for the stealth capabilities of ships in low-temperature environments at sea.

[0090] Step 3: When the ambient temperature is between the first and second preset temperatures (e.g., 25℃~40℃), or the sunlight intensity is between the first and second preset light intensities (e.g., 0.3~0.7 Sun), the actuator film material undergoes partial reversible bending deformation due to the thermal strain mismatch between the PTFE layer and the MXene layer, partially exposing the thermochromic ink layer. At this time, the exposed ink layer exhibits the first visible light color (low-temperature blue), while the actuator film material exhibits a moderate infrared radiation intensity (approximately 0.5-0.6), enabling the target object to blend into the low-irradiance background (such as a cloudy sea surface or a dawn / dusk environment).

[0091] Step 4: When the ambient temperature exceeds the second preset temperature (e.g., 45°C) or the sunlight intensity exceeds the second preset light intensity (e.g., 0.8 Sun), the actuator film material undergoes a fully reversible bending deformation, completely exposing the thermochromic ink layer to the outside. Simultaneously, under temperature stimulation, the thermochromic ink layer rapidly (approximately 2-5 seconds) switches from blue to a second visible light color (yellow), and the ink layer possesses high infrared emissivity (approximately 0.8-0.9), matching the infrared radiation characteristics of the target object with a high-irradiance background (such as a beach or desert), thereby achieving adaptive stealth in both visible and infrared bands.

[0092] To visually verify the above method, a simulation of a real sea-to-sand transition scenario is presented: (1) Simulated ship / sea surface scene (low temperature / low light): The background is a simulated ship with a gray coating and a sea surface, with an ambient temperature of 20℃ and low light (0.2 Sun). After the simulated target (36℃) is covered with an actuation film, the material spreads out flat and appears white, and infrared fusion is achieved to camouflage the ship background.

[0093] (2) Simulate a low irradiance scene (medium temperature / medium light): ambient temperature 30℃, 0.5 Sun, the material is partially flipped to reveal blue, matching the low irradiance sky / sea background.

[0094] (3) Simulated beach scene (high temperature / strong light): The ambient temperature is above 45℃, 1 Sun, the material is completely flipped and turns yellow, the infrared emissivity increases, and it blends with the high temperature beach background.

[0095] The above demonstration shows that, using the actuation film material of this invention, through a simple covering / lamination operation, three-segment adaptive dual-band stealth and thermal management functions can be achieved by utilizing the material's own reversible deformation and thermochromic properties in response to changes in ambient temperature and light intensity. This method requires no external energy or human intervention and is applicable to fields such as military camouflage, individual soldier equipment, and ship coatings.

[0096] This application is based on the synergistic effect of the following five fundamental principles: (1) Infrared stealth principle: Infrared detectors identify targets by utilizing the difference in infrared radiation energy between the target and the background. The infrared radiation energy of a target surface is proportional to the fourth power of its surface emissivity and temperature. For gray body materials, absorptivity equals emissivity. Infrared stealth requires materials to have low infrared absorptivity (i.e., low infrared emissivity). Materials with high carrier concentration and migration rate (such as MXene) have low infrared emissivity. When the target object's temperature is higher than the background, the low emissivity reduces the energy it radiates outward, thus blending with the low-temperature background. When the target object's temperature is lower than the background, the high emissivity increases the energy it radiates outward, and combined with the high temperature to supplement the radiation energy, thus blending with the high-irradiance background.

[0097] (2) Principle of sunlight reflection: The pore size (about 0.1-1μm) of the nanoporous membrane (such as nPTFE) matches the wavelength of visible light, which can cause strong Mie scattering, thus efficiently reflecting sunlight and presenting a white appearance.

[0098] (3) Infrared radiation transmission principle: PTFE and nanoporous membranes have only simple chemical groups in the 8-14μm atmospheric window and weak molecular vibration absorption, so they have high infrared transmittance and do not affect the infrared modulation function of the internal MXene layer.

[0099] (4) Actuation principle (core support for "interlayer thermal strain mismatch"): The PTFE layer has a high coefficient of thermal expansion (approximately 10) when the temperature changes. -4 The coefficient of thermal expansion of the MXene layer is on the order of / K, while the coefficient of thermal expansion of the MXene layer is relatively low (approximately 10). -6 The strain is on the order of / K, resulting in a significant strain mismatch between the two layers. As the temperature rises, the PTFE layer expands more, but due to the constraint of the high-modulus MXene layer, the composite system generates bending stress, driving the material to bend towards the MXene layer. The deformation amplitude is proportional to the layer-to-thickness ratio, modulus ratio, and temperature change. The actuation amplitude can be optimized by adjusting the MXene layer thickness (e.g., 40-60 μm). This reversible deformation process allows the material to exhibit different spatial configurations at different temperatures, thereby simultaneously switching between infrared emissivity (exposing the high-emissivity ink layer after bending) and visible light color.

[0100] (5) Visible light camouflage principle: The thermochromic ink layer appears blue at low temperatures (matching seawater / sky) and turns yellow at high temperatures (≥45℃) (matching beach / sand). This color change is achieved by the reversible protonation reaction of the crystal violet lactone-bisphenol A-octadecyl alcohol system, which has a fast response speed and good reversibility.

[0101] Based on the above principles, this application achieves three-stage adaptive camouflage: flat spreading under low temperature / low light (white + low emissivity), partial flipping under medium temperature / medium light (blue + medium emissivity), and complete flipping and color change under high temperature / strong light (yellow + high emissivity), thereby adaptively matching different scenes such as ships, low-irradiance backgrounds, and beaches.

[0102] Compared with existing technologies, this application has the following advantages: 1. For the first time, it achieves reversible synchronous switching between infrared emissivity and visible light color in a single material system, solving the inherent contradiction of infrared-visible dual-band compatible stealth. 2. It has three-stage environmental adaptability: depending on the temperature and light intensity, it automatically presents three states: flat spread (white / low emissivity), partially flipped (blue / medium emissivity), and completely flipped and color-changing (yellow / high emissivity), respectively matching backgrounds such as shipboard backgrounds, low-irradiance backgrounds, and high-irradiance backgrounds such as beaches, without the need for external energy or manual intervention. 3. Excellent moisture and salt resistance: the surface is superhydrophobic (contact angle 152°), resistant to salt residue and oxidative degradation, and its performance decays very little after immersion in seawater for 30 days, making it suitable for high-humidity and high-salt environments such as the ocean. 4. It also has personal thermal management functions: it keeps the wearer warm in low-temperature environments (photothermal conversion heating) and dissipates heat in high-temperature environments (actuated enhanced convection and radiation heat dissipation), improving wearable thermal comfort. 5. Simple preparation process, easy to scale up: Utilizing scraping and spraying processes, no complex equipment is required, and costs are controllable. 6. Simple and adaptive application method: Simply cover the target surface with the material, and it will automatically switch between dual-band stealth based on ambient temperature and light intensity, requiring no manual intervention or external energy source.

[0103] It should be understood that the phrase "an embodiment" or "one embodiment" throughout the specification means that a specific feature, structure, or characteristic related to the embodiment is included in at least one embodiment of this application. Therefore, "in one embodiment" or "in an embodiment" appearing throughout the specification do not necessarily refer to the same embodiment. Furthermore, these specific features, structures, or characteristics can be combined in any suitable manner in one or more embodiments. It should be understood that in the various embodiments of this application, the sequence numbers of the above-described processes do not imply a sequential order of execution; the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of this application. The sequence numbers of the above-described embodiments are merely descriptive and do not represent the superiority or inferiority of the embodiments.

[0104] It should be noted that, in this document, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Unless otherwise specified, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes that element.

[0105] The above description is merely an embodiment of this application, but the scope of protection of this application is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in this application should be included within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the scope of the claims.

Claims

1. An actuator membrane material with dynamic infrared-visible light stealth, moisture and salt resistance, and thermal management functions, characterized in that, The actuation membrane material has a multilayer asymmetric structure, comprising a nanoporous membrane layer, a transition metal carbide / nitride MXene layer, and a polytetrafluoroethylene (PTFE) layer; wherein: The nanoporous membrane layer and the PTFE layer are located on opposite sides of the MXene layer, and the surface of the PTFE layer facing away from the MXene layer is coated with a thermochromic ink layer. The actuation film material undergoes reversible deformation through interlayer thermal strain mismatch driven by temperature changes, thereby achieving synchronous control of infrared emissivity and visible light reflectivity.

2. The actuation membrane material according to claim 1, characterized in that, The nanoporous membrane is one of the following: PTFE membrane, polyethylene membrane, or nylon membrane.

3. The actuation membrane material according to claim 1, characterized in that, The thickness of the nanoporous membrane layer is 20–50 μm, the thickness of the MXene layer is 40–60 μm, the thickness of the PTFE layer is 50–70 μm, the thickness of the thermochromic ink layer is 30–50 μm, and the overall thickness of the actuation membrane material is 140–230 μm.

4. The actuation membrane material according to claim 1, characterized in that, The thermochromic ink layer contains crystal violet lactone, bisphenol A, octadecyl alcohol microcapsules and yellow pigment, and achieves reversible color switching from blue to yellow within the range of 40-50°C.

5. The actuation membrane material according to any one of claims 1 to 4, characterized in that, On a 36°C hot plate, the actuation angle of the actuation membrane material reaches more than 150°.

6. A method for preparing an actuator film material with dynamic infrared-visible light stealth, moisture and salt resistance, and thermal management functions, characterized in that, Includes the following steps: Preparation of MXene slurry; One-sided hydrophilic modification of PTFE membranes and nanoporous membranes; Thermochromic ink is sprayed onto one side of the PTFE membrane. as well as The prepared MXene slurry is composited between the hydrophilically modified nanoporous membrane and the PTFE membrane to prepare an actuation membrane material with a three-layer asymmetric structure consisting of a nanoporous membrane layer, an MXene layer, and a PTFE layer.

7. The preparation method according to claim 6, characterized in that, The step of preparing MXene slurry further includes: Titanium aluminum carbide (Ti3AlC2) powder was added to concentrated hydrochloric acid (HCl) containing dissolved lithium fluoride (LiF), and the mixture was etched at 35–40 °C for 36–48 hours to obtain titanium carbide (Ti3C2T). x suspension; Filter and wash with water, then centrifuge at 5000–10000 rpm until the pH value is close to 7; and The mixture was sonicated under nitrogen and ice bath conditions for 0.5–1 hour and centrifuged at 2500–4000 rpm for 0.5–1 hour to obtain a suspension of one or more layers of MXene.

8. The preparation method according to claim 6, characterized in that, The single-sided hydrophilic modification step further includes: Dopamine hydrochloride was dissolved in Tris buffer solution to prepare a dopamine buffer solution with a pH of 7–9. The nanoporous membrane and PTFE membrane are soaked in the dopamine buffer solution for 12 to 36 hours to form a hydrophilic polydopamine coating on one side.

9. The preparation method according to claim 6, characterized in that, The preparation steps of the actuation membrane material further include: The MXene slurry was uniformly coated onto the hydrophilic modified surface of the PTFE membrane in a single direction using a scraper, so that the thickness of the dried MXene layer reached 40-60 μm. A nanoporous membrane was composited onto the surface of the MXene layer and dried at room temperature to obtain the actuation membrane material.

10. A method for applying an actuating membrane material, characterized in that, The actuating membrane material is the actuating membrane material according to any one of claims 1 to 5, or the actuating membrane material prepared by the preparation method according to any one of claims 6 to 9, wherein the method includes the following steps: Step 1: Cover or adhere the actuation membrane material to the outer surface of the target object, with the nanoporous membrane layer facing outwards; Step 2: When the ambient temperature is lower than the first preset temperature or the sunlight intensity is lower than the first preset light intensity, the actuation membrane material is kept in a flat and spread state, the nanoporous membrane layer faces outward and presents a white appearance, and the MXene layer provides low infrared emissivity, so that the target object and the background can achieve camouflage and fusion in the visible light and infrared bands. Step 3: When the ambient temperature is between the first preset temperature and the second preset temperature, or when the sunlight intensity is between the first preset light intensity and the second preset light intensity, the actuation film material undergoes partial reversible bending deformation due to interlayer thermal strain mismatch, causing the thermochromic ink layer to be partially exposed and displaying the first visible light color. At the same time, the actuation film material displays low radiation intensity, allowing the target object to blend and camouflage with the low-irradiance background. Step 4: When the ambient temperature is higher than the second preset temperature or the sunlight intensity is higher than the second preset light intensity, the actuation film material undergoes a fully reversible bending deformation due to interlayer thermal strain mismatch, so that the thermochromic ink layer is completely exposed to the outside. Under temperature stimulation, the thermochromic ink layer switches from the first visible light color to the second visible light color. At the same time, the actuation film material exhibits high infrared radiation intensity, so that the target object blends into the high-irradiance background for camouflage.